Antithrombotic dose: Some observations from published clinical trials. Issue 10 (1st July 2019) - Dimmitt, Simon B.; Floyd, Christopher N.; Ferner, Robin E.
Abstract : The clinical doses of antithrombotics—antiplatelet and anticoagulant agents—need to balance efficacy and safety. It is not clear from the published literature how the doses currently used in clinical practice have been derived from preclinical and clinical data. There are few large randomised controlled trials (RCTs) that compare outcomes with different doses vs placebo. For newer antithrombotics, RCT doses appear to have been chosen to maximise the probability of demonstrating noninferiority when compared to established agents such as warfarin or clopidogrel. Data from RCTs show that aspirin is an effective antithrombotic at doses below 75 mg daily, and that direct oral anticoagulants reduce the risk of stroke in patients with coronary disease at doses 1/4 of those recommended in atrial fibrillation. Lower doses than those currently recommended are safer and still maintain substantial efficacy.